A co-ownership healthy canteen, a school-based innovation to tackle anemia among high school girls in Kota Yogyakarta - Yasinta, Riesta (Berita Kedokteran Masyarakat, 2021)
Objective: This purpose of this initiative program is to promote healthy and balanced nutrition meals for students consisting of vegetables and fish as the food of choice to prevent anemia Content: High school girls who live in a growing city like Kota Yogyakarta, have a high risk of developing anemia. They are not only familiar with modern and unhealthy lifestyles, but also have abundant access to high-energy low nutrition foods. Based on a local health survey conducted in 2012, one-third of young women in Kota Yogyakarta (35,2%) suffered from anemia. The condition even exacerbated with the less supportive school environment such as unhealthy meals and snacks in the school canteen. The ideas are to grow vegetables and raise fishes at school. Students build vegetable gardens, adopting the green vertical garden concept that is widely implemented in the densely populated city of Kota Yogyakarta. Fishes’ pond is built in school as an alternative way to manage and reuse the ablution water. the products can be processed by the school’s canteen into affordable and healthy meals for students. The healthy canteen concept transforms ordinary school canteen into a place for promoting vegetables and fish as a food of choice to prevent anemia. The canteen’s keeper and students’ council share cost and profit as a form of co-ownership. This program will be integrated with the students’ council’s entrepreneurship program. A combination between the co-ownership healthy canteen and iron supplementation may result in a greater impact to combat adolescents’ anemia in Kota Yogyakarta.